Selective texturing and cleaning process, IBC solar cell and preparation method thereof
The preparation of different suede structures in IBC solar cells through selective fleece cleaning process solves the problems of complex process and high cost, and improves the accuracy and electrical performance of the battery.
Patent Information
- Application Number
- CN202311262213.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-01
AI Technical Summary
The process of IBC solar cells is complicated, resulting in high production costs and difficult to meet the different design requirements of the emitter and base zone at the same time.
The selective velvet cleaning process is adopted to form a laser ablation structure with different energy fluxes on the surface of the silicon wafer, and combined with alkaline washing and pickling washing steps to form an appropriate suede structure to improve the accuracy and electrical performance of the battery.
This process can selectively prepare different suede structures, improve the accuracy and electrical performance of IBC solar cells, and reduce production costs.
Smart Images

Figure CN119744014A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a selective texturing and cleaning process, an IBC solar cell and a preparation method thereof. Background Art
[0002] The most notable feature of the interdigitated back contact (IBC) solar cell is that the PN junction and metal contact are both on the back of the solar cell, and the front surface completely avoids the shielding of the metal grid electrode. Combined with the pyramid velvet structure on the front surface and the light trapping structure composed of the anti-reflection layer, it can maximize the use of incident light, reduce optical losses, and have a higher short-circuit current. At the same time, the back uses an optimized metal grid electrode to reduce the series resistance. Usually the front surface uses SiN x / SiO x The double-layer film not only has an anti-reflection effect, but also has a good passivation effect on the suede silicon surface. Currently, IBC solar cells are the most complex in process and the most difficult in structural design among commercial crystalline silicon cells. The HBC and TBC technologies that combine IBC solar cells with crystalline silicon heterojunction (HJT) solar cells or TOPCon technology can further improve the efficiency of the cells.
[0003] Although IBC solar cells have many advantages, they also face many challenges: 1. The process is complicated. The cross-shaped p-region and n-region on the back require multiple masks and photolithography techniques during the production process. In order to prevent leakage, the gap area between the p-region and the n-region also needs to be very precise, which increases the difficulty of the process. 2. The complex process steps of IBC make its production cost much higher than that of traditional crystalline silicon cells. Summary of the invention
[0004] Based on this, it is necessary to provide a selective texturing and cleaning process, an IBC solar cell and a preparation method thereof to address the above problems; the process can selectively prepare different texturing structures, so that the prepared IBC solar cell can simultaneously meet different design requirements for the emitter and base region, and improve the precision and electrical performance of the IBC solar cell.
[0005] A selective velveting cleaning process comprises the following steps:
[0006] A tunnel oxide layer and a polysilicon layer are sequentially formed on a first surface and a second surface opposite to the silicon wafer;
[0007] diffusing the polysilicon layer on the second surface;
[0008] Lasers with energy fluxes of F1 and F2 are used to ablate different positions of the second surface, thereby correspondingly forming a primary ablation structure and a secondary ablation structure, wherein F1 is 3000 μJ / mm 2 -12000μJ / mm 2 , F2 is 500μJ / mm 2 -3000μJ / mm 2 , and F1>F2;
[0009] After the ablation is completed, the tunnel oxide layer and the polysilicon layer on the first surface are removed to obtain a prefabricated silicon wafer;
[0010] The prefabricated silicon wafer is sequentially subjected to alkali washing and acid washing, so that a groove for preparing a gate line is formed at the primary ablation structure, and a mark point is formed at the secondary ablation structure.
[0011] In one embodiment, the difference between F1 and F2 is greater than or equal to 2000 μJ / mm 2 .
[0012] In one embodiment, the laser is selected from picosecond laser.
[0013] In one of the embodiments, in the step of diffusing the polysilicon layer on the second surface, a doped glass layer is formed, and the thickness of the doped glass layer is 10 nm-100 nm.
[0014] In one embodiment, for every 1 nm increase in the doped glass layer, F1 and F2 are increased by 30 μJ / mm 2 -90μJ / mm 2 .
[0015] In one embodiment, the solution used for alkali washing is selected from a sodium hydroxide solution, and the mass fraction of sodium hydroxide in the sodium hydroxide solution is 1%-5%.
[0016] In one embodiment, the solution used for pickling is selected from hydrofluoric acid solution and / or nitric acid solution.
[0017] In one embodiment, the alkali washing is carried out at a temperature of 75°C-88°C and for a time of 300s-600s.
[0018] A method for preparing an IBC solar cell includes the selective texturing and cleaning process as described above.
[0019] An IBC solar cell manufactured by the above-mentioned method for manufacturing an IBC solar cell, wherein the grid line offset ratio of the IBC solar cell is less than 1%.
[0020] The selective texturing cleaning process of the present invention adopts an energy flux of 3000 μJ / mm 2 -12000μJ / mm 2 The laser can destroy the crystal structure of the doped polysilicon layer, the tunnel oxide layer, and the surface of the silicon wafer under the tunnel oxide layer, so that the silicon wafer at the first ablation structure forms crystalline silicon with surface lattice damage. At the same time, the energy flux is 500μJ / mm 2 -3000μJ / mm 2 The laser can destroy the tunneling oxide layer and the doped polysilicon layer, making the dense tunneling oxide layer and the doped polysilicon layer structure loose, and ensure that the silicon wafer under the tunneling oxide layer is not damaged.
[0021] Furthermore, after removing the tunneling oxide layer and the polysilicon layer on the opposite surface of the doped polysilicon layer, alkaline washing and acid washing are performed in sequence, which not only forms a polished surface at the primary ablation structure to enhance the passivation effect, but also makes the velvet size formed at the secondary ablation structure as high as about 0.2μm-0.6μm, which is beneficial to improve the recognition accuracy of the camera under the polishing background, thereby improving the accuracy of the laser alignment groove and printing alignment, and can also simultaneously form a light-trapping velvet surface on the surface of the silicon wafer where the tunneling oxide layer and the polysilicon layer are removed, which is beneficial to increase the current.
[0022] Therefore, different velvet structures can be selectively produced through the process provided by the present invention, so that the produced IBC solar cell can simultaneously meet different design requirements for the emitter and the base region, and improve the precision and electrical performance of the IBC solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a flow chart of the selective texturing and cleaning process of the present invention;
[0024] Figure 2 This is a surface morphology diagram of the gate line area and the mark point area after texturing and cleaning in Example 1 of the present invention, wherein a is the surface morphology diagram of the gate line area, and b is the surface morphology diagram of the mark point area.
[0025] Among them, 101, silicon wafer; 1011, first surface; 1012, second surface; 102, tunneling oxide layer; 103, polysilicon layer; 104, doped polysilicon layer; 105, doped glass layer; 20, primary ablation structure; 30, secondary ablation structure; 40, groove; 50, mark point. DETAILED DESCRIPTION
[0026] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.
[0028] Combination Figure 1 As shown, the present invention provides a selective texturing cleaning process, comprising the following steps:
[0029] S1, sequentially preparing a tunnel oxide layer 102 and a polysilicon layer 103 on a first surface 1011 and a second surface 1012 opposite to each other of a silicon wafer 101;
[0030] S2, diffusing the polysilicon layer 103 on the second surface 1012;
[0031] S3, lasers with energy fluxes F1 and F2 are used to ablate different positions of the second surface 1012, thereby correspondingly forming a primary ablation structure 20 and a secondary ablation structure 30, wherein F1 is 3000 μJ / mm 2 -12000μJ / mm 2 , F2 is 500μJ / mm 2 -3000μJ / mm 2 , and F1>F2;
[0032] S4, after the ablation is completed, the tunnel oxide layer 102 and the polysilicon layer 103 on the first surface 1011 are removed to obtain a prefabricated silicon wafer;
[0033] S5 , sequentially washing the prefabricated silicon wafer with alkali and acid, so that a groove 40 for preparing a gate line is formed at the primary ablation structure 20 , and a mark point 50 is formed at the secondary ablation structure 30 .
[0034] In step S1 and step S2, the present invention does not limit the preparation method of the tunneling oxide layer 102, the polysilicon layer 103 and the diffusion of the polysilicon layer 103, and those skilled in the art can prepare them according to the existing technology.
[0035] Specifically, before preparing the tunnel oxide layer 102 and the polysilicon layer 103 , the silicon wafer 101 is first cleaned and polished to remove surface impurities.
[0036] In one embodiment, when the silicon wafer 101 is selected from a P-type silicon wafer and the diffusion process is selected from phosphorus diffusion, the obtained doped polysilicon layer 104 is a phosphorus-doped polysilicon layer, and the formed doped glass layer 105 is a phosphorus silicon glass layer (PSG).
[0037] In step S3, an energy flux of 3000 μJ / mm is used. 2 -12000μJ / mm 2 The laser can destroy the crystal structure of the doped polysilicon layer 104, the tunneling oxide layer 102 and the surface of the silicon wafer 101 under the tunneling oxide layer 102, so that the silicon wafer 101 at the first ablation structure forms crystalline silicon with surface lattice damage. At the same time, the energy flux is 500μJ / mm 2 -3000μJ / mm 2 The laser can destroy the tunnel oxide layer 102 and the doped polysilicon layer 104, making the dense tunnel oxide layer 102 and the doped polysilicon layer 104 structures loose, and ensure that the silicon wafer 101 under the tunnel oxide layer 102 is not damaged.
[0038] Preferably, the difference between F1 and F2 is greater than or equal to 2000 μJ / mm 2 , and further preferably the difference between F1 and F2 is 2000 μJ / mm 2 -6000μJ / mm 2 , which is more conducive to preparing grooves 40 and mark points 50 with different suede structures.
[0039] In one embodiment, the picosecond laser has a high energy peak and a short pulse width, is easier to ablate, and has an obvious step effect at the pattern boundary after ablation and cleaning. Preferably, the laser is selected from a picosecond laser.
[0040] In one embodiment, in the step of diffusing the polysilicon layer on the second surface, the thickness of the formed doped glass layer 105 is preferably 10 nm-100 nm.
[0041] More preferably, for every 1 nm increase in the doped glass layer 105, F1 and F2 are increased by 30 μJ / mm 2 -90μJ / mm 2 , the formation of the primary ablation structure 20 and the secondary ablation structure 30 can be ensured.
[0042] In step S4, the present invention does not limit the method for removing the tunnel oxide layer 102 and the polysilicon layer 103 on the first surface, and those skilled in the art can prepare it according to the prior art.
[0043] In one embodiment, the tunnel oxide layer 102 and the polysilicon layer 103 are preferably removed by pickling etching, wherein the solution used for pickling is selected from a mixed solution of hydrofluoric acid and / or nitric acid, and more preferably a mixed solution of hydrofluoric acid and nitric acid.
[0044] In step S5, after alkali washing, not only a polished surface is formed at the primary ablation structure 20 to enhance the passivation effect, but also the velvet size formed at the secondary ablation structure 30 is as high as about 0.2μm-0.6μm, which is beneficial to improve the recognition accuracy of the camera under the polishing background, thereby improving the accuracy of laser alignment grooving and printing alignment, and can also form a light-trapping velvet on the first surface 1011 at the same time, which is beneficial to increase the current. In addition, during the alkali washing process, due to the presence of the doped glass layer 105, the un-ablated doped polysilicon layer 104 can be effectively prevented from being corroded by alkali, which is beneficial to ensure the integrity of the patterned structure, thereby improving the accuracy. Furthermore, acid washing after alkali washing can not only remove the doped glass layer 105, but also help to further remove damage and contamination.
[0045] It should be noted that, combined with Figure 1 As shown, the groove 40 penetrates the tunnel oxide layer 102 and the doped polysilicon layer 104 and extends to the inside of the silicon wafer 101 ; the mark point 50 penetrates the tunnel oxide layer 102 and the doped polysilicon layer 104 and forms a velvet surface on the second surface 1012 of the silicon wafer 101 .
[0046] Preferably, the solution for alkali washing is selected from a sodium hydroxide solution, wherein the mass fraction of sodium hydroxide in the sodium hydroxide solution is 1%-5%, which is more conducive to completely removing the primary ablation structure 20 and the secondary ablation structure 30, ensuring the integrity of the patterned structure, and facilitating improving the precision.
[0047] In one embodiment, the solution for alkaline washing further includes a texturing additive, the volume of which is 0.3%-1.5% of the volume of the alkaline washing solution, and the texturing additive is beneficial for protecting the tunneling oxide layer.
[0048] In one embodiment, the alkali washing is carried out at a temperature of 75° C. to 88° C. for 300 s to 600 s.
[0049] Preferably, the solution used for pickling is selected from hydrofluoric acid solution and / or nitric acid solution, more preferably a mixed solution of hydrofluoric acid and nitric acid.
[0050] The present invention also provides a method for preparing an IBC solar cell, comprising the selective texturing and cleaning process as described above.
[0051] The present invention does not limit the preparation method of the IBC solar cell after the selective texturing and cleaning process, and those skilled in the art can prepare it according to the existing technology.
[0052] In one embodiment, after a selective texturing and cleaning process, a complete IBC solar cell structure can be obtained through specific preparation steps such as double-sided aluminum oxide passivation treatment, double-sided silicon nitride coating treatment, laser window opening and screen printing, which will not be described in detail in the present invention.
[0053] Based on the selective texturing and cleaning process described in the present invention, different velvet structures can be selectively prepared. In the laser window opening and screen printing preparation steps, the offset distance between printing and laser is made less than 40 μm, thereby improving the precision and electrical performance of the IBC solar cell.
[0054] The present invention also provides an IBC solar cell manufactured by the above-mentioned IBC solar cell manufacturing method, wherein the grid line offset ratio of the IBC solar cell is less than 1%.
[0055] Different velvet structures can be selectively produced by the process provided by the present invention, so that the produced IBC solar cell can simultaneously meet different design requirements for the emitter and the base region, and improve the precision and electrical performance of the IBC solar cell.
[0056] Hereinafter, the selective texturing and cleaning process, the IBC solar cell and the preparation method thereof will be further described through the following specific embodiments.
[0057] Example 1
[0058] A 182P type high minority carrier silicon wafer (resistivity of 1.0Ω·cm) was selected and polished with a NaOH solution. The weight loss of the silicon wafer was measured to be 0.3g. A tunneling oxide layer and a polysilicon layer were prepared in sequence. The thickness of any tunneling oxide layer was 1.4nm, and the thickness of any polysilicon layer was 140nm.
[0059] Phosphorus diffusion is performed on any polysilicon layer to obtain a doped polysilicon layer and a phosphosilicate glass layer. The square resistance of the doped polysilicon layer is measured to be 38, and the thickness of the phosphosilicate glass layer is 40 nm.
[0060] IBC laser pattern was selected, which included main grid, sub grid and 4 mark points. The energy flux was 5500μJ / mm 2 Picosecond laser ablation is used to form a primary ablation structure with an energy flux of 1600 μJ / mm 2 Picosecond laser ablation is performed to form a secondary ablation structure.
[0061] After the ablation is completed, a mixed solution of hydrofluoric acid and nitric acid is used for wrap-around cleaning, and a chain machine is used to remove the polysilicon layer and the tunnel oxide layer on the opposite surface of the doped polysilicon layer. The tested weight loss is 0.1g.
[0062] A 1% mass fraction NaOH solution was used, and a texturing additive for protecting the oxide layer was added. The volume of the texturing additive was 1% of the volume of the NaOH solution. Texturing cleaning was performed at 80°C for 400s. After the texturing cleaning, the size of the velvet formed on the front of the silicon wafer was about 1.5μm, the weight loss was 0.3g, and the reflectivity was 9.3%. A groove with a polished surface was formed at the first ablation structure, namely the gate line area, and a mark point with a velvet surface was formed at the second ablation structure. The velvet size was about 0.5μm. Furthermore, the gate line area and the mark point area formed after the texturing cleaning were tested for surface morphology. The results are as follows: Figure 2 As shown, a is the surface morphology of the grid line area, proving that it is a polished surface, which can provide better passivation effect compared with the pyramid velvet surface; b is the surface morphology of the mark point area, proving that it is a light-trapping velvet surface, which has a high recognition degree under the polishing background, which is beneficial to improve the camera recognition accuracy, and then can improve the accuracy of laser grooving and printing alignment, and improve the accuracy and electrical performance of IBC solar cells.
[0063] ALD equipment is used to coat the double-sided aluminum oxide layer, and PECVD equipment is used to coat the double-sided silicon nitride layer. The mark points prepared above are used for alignment, and the laser marking and grooving are accurately overlapped in the auxiliary grid line area prepared above to ablate the silicon nitride film. Based on the clear, high-contrast velvet mark points prepared above, the laser grooving alignment success rate reaches 99.2%, and the laser alignment error is less than 20μm. Further, the mark points prepared above are precisely aligned, and silver electrodes and aluminum grid lines are printed in the laser grooved P area, and silver grid lines are printed in the N area, and the silver-aluminum auxiliary grid lines are arranged in a cross pattern. After printing and sintering, the printing offset ratio is less than 0.5%.
[0064] Example 2
[0065] The doped polysilicon layer and the phosphosilicate glass layer were prepared by the same preparation method as in Example 1.
[0066] IBC laser pattern was selected, which included main grid, sub grid and 4 mark points. The energy flux was 7500μJ / mm 2 Picosecond laser ablation is used to form a primary ablation structure with an energy flux of 1600 μJ / mm 2 Picosecond laser ablation is performed to form a secondary ablation structure.
[0067] After the ablation is completed, a mixed solution of hydrofluoric acid and nitric acid is used for wrap-around cleaning, and a chain machine is used to remove the polysilicon layer and the tunnel oxide layer on the opposite surface of the doped polysilicon layer. The tested weight loss is 0.1g.
[0068] A NaOH solution with a mass fraction of 1% was used, and a texturing additive for protecting the oxide layer was added. The volume of the texturing additive was 1% of the volume of the NaOH solution. Texturing cleaning was carried out at 80°C for 400s. After the texturing cleaning, the velvet size formed on the front of the silicon wafer was about 1.5μm, the weight was reduced by 0.3g, and the reflectivity was 9.3%. A groove with a polished surface was formed at the first ablation structure, namely the gate line area, and a mark point with a velvet surface was formed at the second ablation structure. The velvet size was about 0.4μm.
[0069] ALD equipment is used to coat the double-sided aluminum oxide layer, and PECVD equipment is used to coat the double-sided silicon nitride layer. The mark points prepared above are used for alignment, and the laser marking and grooving are accurately overlapped in the auxiliary grid line area prepared above to ablate the silicon nitride film. Based on the clear, high-contrast velvet mark points prepared above, the laser grooving alignment success rate reaches 99.2%, and the laser alignment error is less than 20μm. Further, the mark points prepared above are precisely aligned, and silver electrodes and aluminum grid lines are printed in the laser grooved P area, and silver grid lines are printed in the N area, and the silver-aluminum auxiliary grid lines are arranged in a cross pattern. After printing and sintering, the printing offset ratio is less than 0.5%.
[0070] Example 3
[0071] The doped polysilicon layer and the phosphosilicate glass layer were prepared by the same preparation method as in Example 1.
[0072] IBC laser pattern is selected, the pattern includes main grid, sub grid and 4 mark points. The energy flux is 3000μJ / mm 2 The nanosecond laser ablation is used to form a primary ablation structure, with an energy flux of 500 μJ / mm 2 Nanosecond laser ablation is used to form a secondary ablation structure.
[0073] After the ablation is completed, a mixed solution of hydrofluoric acid and nitric acid is used for wrap-around cleaning, and a chain machine is used to remove the polysilicon layer and the tunnel oxide layer on the opposite surface of the doped polysilicon layer. The tested weight loss is 0.1g.
[0074] A NaOH solution with a mass fraction of 5% was used, and a texturing additive for protecting the oxide layer was added. The volume of the texturing additive was 1% of the volume of the NaOH solution. Texturing cleaning was carried out at 75°C for 600s. After the texturing cleaning, the velvet size formed on the front of the silicon wafer was about 1.5μm, the weight was reduced by 0.3g, and the reflectivity was 9.3%. A groove with a polished surface was formed at the first ablation structure, namely the gate line area, and a mark point with a velvet surface was formed at the second ablation structure. The velvet size was about 2μm.
[0075] ALD equipment is used to coat the double-sided aluminum oxide layer, and PECVD equipment is used to coat the double-sided silicon nitride layer. The mark points prepared above are used for alignment, and the laser marking and grooving are accurately overlapped in the auxiliary grid line area prepared above to ablate the silicon nitride film. Based on the clear, high-contrast velvet mark points prepared above, the laser grooving alignment success rate reaches 99%, and the laser alignment error is less than 40μm. Further, the mark points prepared above are precisely aligned, and silver electrodes and aluminum grid lines are printed in the laser grooved P area, and silver grid lines are printed in the N area, and the silver-aluminum auxiliary grid lines are arranged in a cross pattern. After printing and sintering, the printing offset ratio is less than 1%.
[0076] Example 4
[0077] The doped polysilicon layer and the phosphosilicate glass layer were prepared by the same preparation method as in Example 1.
[0078] IBC laser pattern is selected, the pattern includes main grid, sub grid and 4 mark points. The energy flux is 12000μJ / mm 2 Picosecond laser ablation is used to form a primary ablation structure, with an energy flux of 3000μJ / mm 2 Picosecond laser ablation is performed to form a secondary ablation structure.
[0079] After the ablation is completed, a mixed solution of hydrofluoric acid and nitric acid is used for wrap-around cleaning, and a chain machine is used to remove the polysilicon layer and the tunnel oxide layer on the opposite surface of the doped polysilicon layer. The tested weight loss is 0.1g.
[0080] A NaOH solution with a mass fraction of 5% was used, and a texturing additive for protecting the oxide layer was added. The volume of the texturing additive was 1% of the volume of the NaOH solution. Texturing cleaning was carried out at 85°C for 300s. After the texturing cleaning, the velvet size formed on the front of the silicon wafer was about 1.5μm, the weight was reduced by 0.3g, and the reflectivity was 9.3%. A groove with a polished surface was formed at the first ablation structure, namely the gate line area, and a mark point with a velvet surface was formed at the second ablation structure. The velvet size was about 1.9μm.
[0081] ALD equipment is used to coat the double-sided aluminum oxide layer, and PECVD equipment is used to coat the double-sided silicon nitride layer. The mark points prepared above are used for alignment, and the laser marking and grooving are accurately overlapped in the auxiliary grid line area prepared above to ablate the silicon nitride film. Based on the clear, high-contrast velvet mark points prepared above, the laser grooving alignment success rate reaches 99%, and the laser alignment error is less than 40μm. Further, the mark points prepared above are precisely aligned, and silver electrodes and aluminum grid lines are printed in the laser grooved P area, and silver grid lines are printed in the N area, and the silver-aluminum auxiliary grid lines are arranged in a cross pattern. After printing and sintering, the printing offset ratio is less than 1%.
[0082] Example 5
[0083] The doped polysilicon layer and the phosphosilicate glass layer were prepared by the same preparation method as in Example 1.
[0084] IBC laser pattern is selected, the pattern includes main grid, sub grid and 4 mark points. The energy flux is 4000μJ / mm 2 The laser ablation is used to form a primary ablation structure, and the energy flux is 2500μJ / mm 2 The laser is used for ablation to form a secondary ablation structure.
[0085] After the ablation is completed, a mixed solution of hydrofluoric acid and nitric acid is used for wrap-around cleaning, and a chain machine is used to remove the polysilicon layer and the tunnel oxide layer on the opposite surface of the doped polysilicon layer. The tested weight loss is 0.1g.
[0086] A NaOH solution with a mass fraction of 1% was used, and a texturing additive for protecting the oxide layer was added. The volume of the texturing additive was 1% of the volume of the NaOH solution. Texturing cleaning was carried out at 80°C for 400s. After the texturing cleaning, the velvet size formed on the front of the silicon wafer was about 1.5μm, the weight was reduced by 0.3g, and the reflectivity was 9.3%. A groove with a polished surface was formed at the first ablation structure, namely the gate line area, and a mark point with a velvet surface was formed at the second ablation structure. The velvet size was about 0.8μm.
[0087] ALD equipment is used to coat the double-sided aluminum oxide layer, and PECVD equipment is used to coat the double-sided silicon nitride layer. The mark points prepared above are used for alignment, and the laser marking and grooving are accurately overlapped in the auxiliary grid line area prepared above to ablate the silicon nitride film. Based on the clear, high-contrast velvet mark points prepared above, the laser grooving alignment success rate reaches 96%, and the laser alignment error is less than 45μm. Further, the mark points prepared above are precisely aligned, and silver electrodes and aluminum grid lines are printed in the laser grooved P area, and silver grid lines are printed in the N area, and the silver-aluminum auxiliary grid lines are arranged in a cross pattern. After printing and sintering, the printing offset ratio is less than 2%.
[0088] Example 6
[0089] The difference between Example 6 and Example 3 is that the thickness of the prepared phosphorus silicon glass layer is 80nm, and the energy flux is 6200μJ / mm 2 The laser ablation forms a primary ablation structure with an energy flux of 2100 μJ / mm 2 The laser is used for ablation to form a secondary ablation structure.
[0090] The laser slotting alignment success rate reached 99.3%, and the laser alignment error was less than 20μm. Further, the mark points prepared above were precisely aligned, and silver electrodes and aluminum grid lines were printed in the laser slotted P area, and silver grid lines were printed in the N area, and silver and aluminum auxiliary grid lines were arranged in a cross pattern. After printing and sintering, the printing offset ratio was less than 0.5%.
[0091] Comparative Example 1
[0092] The difference between Comparative Example 1 and Example 1 is that the same energy flux of 4500 μJ / mm 2 Laser ablation is performed to prepare the grid line area and mark points.
[0093] After cleaning, the mark point area and the grid line area both have fine velvet, with a velvet size of about 0.1μm. In addition, in the laser window opening process, because the velvet in the mark point area is less than 0.1μm and very sparse, the camera's point grabbing accuracy is low, the laser slotting alignment success rate is only 76%, and the alignment offset accuracy is less than 35μm; in the screen printing process, due to the large window opening offset, the printing offset ratio is as high as 6%.
[0094] Comparative Example 2
[0095] The difference between Comparative Example 2 and Example 1 is that the same energy flux of 8500 μJ / mm 2 Laser ablation is performed to prepare the grid line area and mark points.
[0096] After cleaning, the mark area and the grid line area are polished. Since the mark area is a polished surface, the background of the P area and the N area are also polished, and there is no obvious contrast between the mark and the background under the alignment camera. The camera's point capture accuracy is very low, the laser slot alignment success rate is only 5%, and the alignment offset accuracy is less than 50μm; in the screen printing process, due to the large window offset, the printing offset ratio is as high as 88%.
[0097] Comparative Example 3
[0098] The difference between Comparative Example 3 and Example 1 is that the energy flux is 3600 μJ / mm 2 The laser is used for ablation to form a secondary ablation structure.
[0099] After cleaning the mark area, a fine velvet surface is obtained, with a velvet size of about 0.15μm. In addition, in the laser window opening process, due to the small velvet surface in the mark area and poor contrast, the camera has many point capture errors, the laser slotting alignment success rate is only 88%, and the alignment offset accuracy is less than 35μm; in the screen printing process, due to the poor alignment accuracy of the laser window opening, the printing offset ratio is as high as 12%.
[0100] Comparative Example 4
[0101] The difference between Comparative Example 4 and Example 1 is that the energy flux is 2500 μJ / mm 2 The laser is used for ablation to form a primary ablation structure.
[0102] After cleaning, the grid line area forms a partial polished surface and a partial small pyramid velvet surface, and the laser grooving alignment success rate, alignment offset accuracy, and printing offset ratio are not much different from those in Example 1. However, due to the low laser energy, a velvet structure is formed in the grid line area, which reduces the back reflection and affects the passivation, resulting in poor electrical performance of the IBC solar cell.
[0103] Comparative Example 5
[0104] The difference between Comparative Example 5 and Example 1 is that the energy flux is 13000 μJ / mm 2 The laser is used for ablation to form a primary ablation structure.
[0105] Since excessive laser energy can cause excessive damage, alkaline cleaning cannot completely remove the damaged layer, forming a high-load area on the cell surface, resulting in poor electrical performance of IBC solar cells.
[0106] The IBC solar cells prepared in Examples 1-6 and Comparative Examples 1-5 were subjected to performance tests, and the results are shown in Table 1.
[0107] Table 1
[0108]
[0109]
[0110] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0111] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A selective texturing and cleaning process, characterized in that: The steps include: A tunnel oxide layer and a polysilicon layer are sequentially formed on a first surface and a second surface opposite to the silicon wafer; diffusing the polysilicon layer on the second surface; Lasers with energy fluxes of F1 and F2 are used to ablate different positions of the second surface, thereby correspondingly forming a primary ablation structure and a secondary ablation structure, wherein F1 is 3000 μJ / mm 2 -12000μJ / mm 2 , F2 is 500μJ / mm 2 -3000μJ / mm 2 , and F1>F2; After the ablation is completed, the tunnel oxide layer and the polysilicon layer on the first surface are removed to obtain a prefabricated silicon wafer; The prefabricated silicon wafer is sequentially subjected to alkali washing and acid washing, so that a groove for preparing a gate line is formed at the primary ablation structure, and a mark point is formed at the secondary ablation structure.
2. The selective texturing cleaning process according to claim 1, characterized in that: The difference between F1 and F2 is greater than or equal to 2000μJ / mm 2 .
3. The selective texturing cleaning process according to claim 1, characterized in that: The laser is selected from picosecond laser.
4. The selective texturing cleaning process according to claim 1, characterized in that: In the step of diffusing the polysilicon layer on the second surface, a doped glass layer is formed, and the thickness of the doped glass layer is 10 nm-100 nm.
5. The selective texturing cleaning process according to claim 4, characterized in that: For every 1nm increase in the doped glass layer, F1 and F2 increase by 30μJ / mm 2 -90μJ / mm 2 .
6. The selective texturing cleaning process according to claim 1, characterized in that: The solution used for alkali washing is selected from a sodium hydroxide solution, and the mass fraction of sodium hydroxide in the sodium hydroxide solution is 1%-5%.
7. The selective texturing cleaning process according to claim 1, characterized in that: The solution used for pickling is selected from a hydrofluoric acid solution and / or a nitric acid solution.
8. The selective texturing cleaning process according to claim 1, characterized in that: The alkali washing is carried out at a temperature of 75°C-88°C and for a time of 300s-600s.
9. A method for preparing an IBC solar cell, characterized in that: It includes the selective texturing and cleaning process as described in any one of claims 1-8.
10. An IBC solar cell manufactured by the method for manufacturing an IBC solar cell according to claim 9, characterized in that: The grid line offset ratio of the IBC solar cell is less than 1%.
Citation Information
Cited By
Back contact battery and processing method thereof
CN120379385A
Solar cell and photovoltaic module
CN120751832A
Solar cell, cleaning method for laser residue of solar cell, and preparation method of solar cell
CN121568450A